Disruption of hnRNP A2-mediated RNA dynamics by amyloid-β drives MBP increase in Alzheimer’s disease - Adhara Gaminde-Blasco; Rodrigo Senovilla-Ganzo; Uxue Balantzategi; Maialen Martinez-Preciado; Estibaliz Capetillo-Zarate; Fernando García-Moreno; Carlos Matute; Jimena Baleriola; Elena Alberdi (Cellular and Molecular Life Sciences)
Abstract Oligodendrocyte dysfunction, myelin degeneration, and white matter changes are critical events in the cognitive decline of Alzheimer’s disease (AD). Amyloid-β peptide (Aβ), a hallmark of AD, disrupts oligodendrocyte and myelin homeostasis, through mechanisms that remain poorly understood. Here, transcriptomic profiling of Aβ-exposed oligodendrocytes revealed widespread gene expression changes, particularly in RNA-related processes. Among these, hnRNP A2, a key regulator of RNA transport and myelin protein regulation, was aberrantly upregulated in hippocampal oligodendrocytess from AD patients with high Aβ levels, from AD mouse models, and in Aβ-treated oligodendrocytes. RNA-immunoprecipitation sequencing of the hnRNP A2 interactome revealed Aβ-induced changes in mRNA interactions, particularly enriched binding to Mbp and Mobp, indicating impaired RNA metabolism of myelin components. Furthermore, Aβ, through hnRNP A2 disruption, increased the number, cargo and dynamics of Mbp- and Mobp-containing granules, enhanced MBP and MOBP synthesis, and decreased oligodendroglial voltage-gated Ca2+ influx in an MBP-dependent manner. These findings suggest that Aβ-induced dysregulation of hnRNP A2 impairs RNA metabolism and myelin protein synthesis, altering the intracellular Ca2+ homeostasis critical for oligodendrocyte function. Graphical abstract